Pemberdayaan Masyarakat dalam Penerapan PHBS untuk Pengendalian Jentik Nyamuk Aedes Aegypti di Kelurahan Sungai Pangeran - Hendawati Hendawati; Haryyan Lukita; Husnul Khotimah; Gabryella Fatima Simanjuntak; Tsaqila, Nibras Qaulan; Estu Aulia (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Dengue Hemorrhagic Fever (DHF) is a contagious disease caused by the Aedes aegypti mosquito, commonly found in Indonesia, particularly in areas with poor environmental sanitation. The implementation of Clean and Healthy Living Behavior (PHBS) is one of the effective strategies for controlling mosquito vectors and preventing DHF. This community service activity aims to improve public understanding and participation in the application of PHBS in Sungai Pangeran Village, Palembang, through counseling, training of Larvae Monitoring Officers (Jumantik), and community clean-up activities with the 3M Plus Movement (Draining, Closing, Burying, and additional measures). The results showed a significant increase in public knowledge about PHBS and active participation in mosquito larvae monitoring. The training of Jumantik created cadres capable of performing independent monitoring, and the community clean-up activities reduced potential mosquito breeding sites by 60%. Monitoring also showed a 35% decrease in DHF cases after the program. This activity has proven effective in raising public awareness and reducing vector-borne disease risks in the local environment. However, continued monitoring and support from local governments are needed to sustain the program.